Gene Expression Analysis Reveals the Concurrent Activation of Proapoptotic and Antioxidant-Defensive Mechanisms in Flavokawain B-Treated Cervical Cancer HeLa Cells - Swee, Keong Yeap; Nadiah, Abu; Akhtar, Muhammad Nadeem; Wan, Yong Ho; Huynh, Ky; Sheau, Wei Tan; Noorjahan Banu, Alitheen; Tunku, Kamarul (SAGE Publications, 2017)
Flavokawain B (FKB) is known to possess promising anticancer abilities. This is demonstrated in various cancer cell lines including HeLa cells. Cervical cancer is among the most widely diagnosed cancer among women today. Though FKB has been shown to be effective in treating cancer cells, the exact molecular mechanism is still unknown. This study is aimed at understanding the effects of FKB on HeLa cells using a microarray-based mRNA expression profiling and proteome profiling of stress-related proteins. The results of this study suggest that FKB induced cell death through p21-mediated cell cycle arrest and activation of p38. However, concurrent activation of antioxidant-related pathways and iron sequestration pathway followed by activation of ER-resident stress proteins clearly indicate that FKB failed to induce apoptosis in HeLa cells via oxidative stress. This effect implies that the protection of HeLa cells by FKB from H2O2–induced cell death is via neutralization of reactive oxygen species.